2001
DOI: 10.1164/ajrccm.163.2.2002088
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Endotoxin and Wheeze in the First Year of Life

Abstract: We examined endotoxin exposure and wheezing episodes during the first year of life in a birth cohort of 499 infants with one or both parents having a history of asthma or allergy. We measured endotoxin in settled dust from the baby's bed, bedroom floor, family room, and kitchen floor within the first 3 mo after birth. The primary outcomes were any wheeze (versus no wheeze), and repeated wheeze (versus one or no report of wheeze). We found a significant univariate association of elevated endotoxin (> or = 100 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
281
7
11

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(324 citation statements)
references
References 33 publications
25
281
7
11
Order By: Relevance
“…Similar to the Boston study, we found both a negative association between endotoxin exposure and eczema and positive association between endotoxin exposure and wheeze (25,32). The decreased risk for eczema and potential "protection" from early atopic disease is consistent with the "hygiene hypothesis."…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to the Boston study, we found both a negative association between endotoxin exposure and eczema and positive association between endotoxin exposure and wheeze (25,32). The decreased risk for eczema and potential "protection" from early atopic disease is consistent with the "hygiene hypothesis."…”
Section: Discussionsupporting
confidence: 86%
“…Results from a relatively small study in metropolitan Denver found an inverse association with endotoxin concentration and atopy (3), while a positive association between endotoxin concentration and wheeze was found in a mixed urban and suburban birth cohort in Boston (32,33). This latter Boston study also found an inverse association between endotoxin and eczema (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were independent of season of home sampling, the baby's age at the time of the visit, gender, the mother's age, insurance type and several risk factors for infant wheeze including: day care attendance (Ball et al, 2000;Stark et al, 2003), endotoxin levels (Park et al, 2001), maternal smoking during pregnancy (Gold et al, 1999;Lannero et al, 2006) and exposure to environmental tobacco smoke (Strachan and Cook, 1997;Stein et al, 1999). Although ''high'' levels of Aspergillus, Cladosporium, and Acrodontium demonstrated positive associations with wheeze in unadjusted analyses (each P value was r0.05), the odds ratios decreased following the addition of season of visit and other covariables.…”
Section: Discussionmentioning
confidence: 70%
“…The mechanism for the protective effect of exposure to farm animals is thought to be via induction of Th1 immune responses (Gereda et al, 2000b). Interestingly, increased exposure to lipopolysaccharides in non-farming domestic environments has been associated with an increased risk of recurrent wheeze during the first year of life in children with a family history of allergy (Park et al, 2001); however, the levels of exposure are substantially less than those experienced by farmers' children. A recent study of rural Iowa children seems to contradict the "hygiene hypothesis" that early-life exposure to farm animals is protective against allergic diseases.…”
Section: ) Indoor Airmentioning
confidence: 99%